Disfunção temporomandibular e hábitos parafuncionais em crianças e adolescentes - Araújo Neto, Manoel Gomes de; Santos, Alisson Sousa; Sousa, Paulo Henrique Martins; Vale, Laryssa Castro; Lopes, Caroline Fernanda de Oliveira Farias; Pinto, Guilherme Gonçalves Silva; Nascimento, Ana Lurdes Avelar; Haidar, Adelzir Malheiros e Silva C. B.; Carvalho, Sarah Tarcísia Rebelo Ferreira de; Gonçalves, Maria Claudia (Headache Medicine, 2017)
Introduction: Temporomandibular dysfunction (DTM) Most of the time is discovered during the adult phase, but its symptoms may be ginearly, even in childhood. Due to large muscular, skeletal and joint transformations present during craniofacial growth, children and adolescents may present signs and symptoms of DTM. Objective: To evaluate the frequency of signs and symptoms and the diagnosis of DTM, as well as the oral parafunctional habits in children and adolescents. Material and Method: Participated in this study 44 children and adolescents, regularly enrolled in the EU school B Luís Viana/germany and at the schoolour World/Bequimão located in the city of São Luís-MA, aged between 10:15 years, were excluded those individuals who have performed preortognáticas surgeries, have done or are conducting or thodontic treatments or for DTM´S, who had suffered trauma to the face and did not present the consent signed by the parents. The severity of the DTM was evaluated with the anamnesico content of Fonseca and the diagnosis of DTM with the diagnostic criterion in research RDC/TMD. This project was approved by the CEUMA University Research Ethics Committee, Opinion No. 1,307,233. All parents and guardians signed the term of consent free and clear. Results: The diagnosis of DTM in children and adolescents was demonstrated and the same wa selevated. The signs and symptoms of DTM and the oral parafunctional habits also presented high frequency and can be used as predictors of the worsening of DTM.